PEER AND SELF ASSESSMENT IN ACCOUNTING EDUCATION (CASE STUDY OF ACCOUNTING EDUCATION IN UPH SURABAYA) - Setiawan, Evelyn (Universitas Negeri Malang, 2016)
An accountant is required to have competence to interpret and communicate the results of his/her thinking properly. Such capabilities could be established from the college time through student involvement in peer and self-assessment. This study analyzed the peer and self-assessment done in financial statements analysis class, which held in accounting study program, UPH Surabaya. The result showed that the peer and self assessment can be run effectively when there is an adequate explanation prior to the assessment.Keywords: peer assessment, self assessment